From COVID-19 to long COVID; the forms of the neurological manifestations - Sana Ahuja; Sufian Zaheer (Journal of Mind and Medical Sciences)
Ever since the SARS-CoV-2 infection was declared a global pandemic in 2020, numerous multisystemic manifestations have been discovered. The COVID-19 is known to cause a wide spectrum of neurological symptoms like fatigue, headache, brain fog, stroke, smell and taste disorders, encephalopathy and neurodegenerative disorders. The neurological manifestations are more prevalent in the post-COVID syndrome or long COVID. The National Institute for Health and Care Excellence and WHO defined Ongoing Symptomatic COVID as 4-12 weeks post infection and post COVID-19 syndrome as persistence of symptoms beyond 12 weeks. So far there are limited data available regarding the pathophysiology of neurological symptoms of prolonged COVID, although neuroinflammation and oxidative damage have been implicated. In this review article, we have highlighted the transition from COVID to long-term COVID, focusing the discussion particularly on neurological complications.